1992
DOI: 10.1111/j.1471-0528.1992.tb13855.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of vasopressin release in women with primary dysmenorrhoea and after oral contraceptive treatment—effect on uterine contractility

Abstract: Objective To study aspects of the aetiology of primary dysmenorrhoea and mechanisms underlying the therapeutic effect in this condition of an oral contraceptive. Intervention Intrauterine pressure was recorded before and during infusion of hypertonic saline (5% NaCl, 0.06 ml/kg/min) over 75 min on the first day of bleeding in women with dysmenorrhoea and after 3 weeks of oral contraceptive treatment. Plasma sampling every 15 min of ongoing infusion for the estimation of osmolality, arginine vasopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 16 publications
(15 reference statements)
3
27
0
1
Order By: Relevance
“…In exploratory analyses we confirmed that oral contraceptives decrease plasma vasopressin levels (Ekstrom et al, 1992;Kostoglou-Athanassiou et al, 1998) and increase plasma cortisol levels (Amin et al, 1980). Therefore, 15 patients taking oral contraceptives were excluded, as were patients with depression in relation to panic disorder.…”
Section: Subjectsmentioning
confidence: 63%
“…In exploratory analyses we confirmed that oral contraceptives decrease plasma vasopressin levels (Ekstrom et al, 1992;Kostoglou-Athanassiou et al, 1998) and increase plasma cortisol levels (Amin et al, 1980). Therefore, 15 patients taking oral contraceptives were excluded, as were patients with depression in relation to panic disorder.…”
Section: Subjectsmentioning
confidence: 63%
“…Sabe-se que, em alguns estudos, os pacientes usaram benzodiazepínicos, porém estes podem inibir o CRH e suprimir a secreção de cortisol e ACTH. Segundo Ekstrom et al 59 e Kostoglou-Athanassiou et al 60 , o uso de contraceptivo oral diminui o nível plasmático de vasopressina (substância que exerce influência no eixo HPA), e segundo Amin et al 61 , há aumento do nível de cortisol. Em alguns estudos, o uso de droga antipsicótica pode influenciar o nível de cortisol e arginina-vasopressina plasmático 62,63 .…”
Section: Discussionunclassified
“…Relcovaptan inhibits vasopressin-induced uterine contractions in nonpregnant healthy volunteers [12]. It also prevents pain of primary dysmenorrhea [13], a condition in which increased vasopressin release is apparently of etiological importance [14][15][16]. In the present study we investigated the effect of blocking vasopressin V 1a receptors by orally administrated relcovaptan on uterine contractions in women with preterm labor.…”
Section: Introductionmentioning
confidence: 97%